Tyramine kinetics and metabolism in cirrhosis. - Faraj, B A (1979)
Hypertyraminemia is common in hepatic cirrhosis and correlates in severity with encephalopathy. The mechanism of cirrhotic hypertyraminemia has not been established. The alternative possibilities are increased production from tyrosine and impaired degradation by monoamine oxidase. This investigation determined the pharmacokinetics of tyramine after an intravenous bolus injections of [3H]-tyramine (180--200 muCi 12 Ci/mmol sp act) in 13 cirrhotics and 9 controls. In normals, [3H]tyramine levels initially declined rapidly (alpha-phase) followed by a slower decline (beta-phase) with an average t 1/2 of 20.8 min. Average normal metabolic clearance rate and production rate were 13.2 liters/min and 15.4 microgram/min, respectively. In cirrhotic patients, the plasma disappearance curve for [3H]tyramine was qualitatively similar to that of the control subjects with no apparent different in beta-t 1/2 (17.2 min). The hypertyraminemia of cirrhosis resulted primarily from overproduction of tyramine, as the production rate (32.0 microgram/min) in these patients was significantly greater (P less than 0.05) than in controls, whereas the metabolic clearance rate remained normal (average 12.2 liters/min). A difference in ratio of tyramine metabolic products was noted as well. Cirrhotics had a high ratio of plasma 4-hydroxyphenylethanol:4-hydroxyphenylacetic acid (60:40 vs. 30:70) as compared with normals. Although the tyramine clearance rates are similar in normals and cirrhotics, different mechanisms may be responsible for catabolism.